Cross-talk between nitric oxide, hydrogen peroxide and calcium in salt-stressed Chenopodium quinoa Willd. At seed germination stage - Hajihashemi, Shokoofeh; Skalicky, Milan; Brestic, Marian; Pavla, Vachová (Plant physiology and biochemistry, 2020)
Seed germination is critical for successful crop production and this growth stage can be very sensitive to salt stress depending on the plant's tolerance mechanisms. The pretreatment of Chenopodium quinoa (quinoa) seeds with CaCl2, H2O2 and sodium nitroprusside (SNP) limited the adverse effect of salt stress on seed germination. The pre-treated seeds showed a significant increase in germination rate, relative germination rate and germination index while the mean germination time was significantly reduced under both optimal and stress conditions. In parallel with seed germination, the negative effect of salt stress on the activity of α-amylase and β-amylase was reduced in pre-treated seeds. The amylase enzymes are responsible for starch hydrolysis, so the reduction of amylase activity by salt stress resulted in higher starch content in the seeds and lower concentrations of water-soluble sugars such as glucose. Pretreatment stimulated amylase activity resulting in starch breakdown and increased content of water-soluble sugars in the salt-stressed seeds. Protein and amino acid contents were significantly enhanced in salt-stressed seeds, which were highlighted in pre-treated seeds. The findings of this study demonstrate that pretreatment of quinoa seeds with CaCl2, H2O2 and SNP at 5, 5 and 0.2 mM, respectively, concentration to achieve rapid germination at high levels under optimal and salt-stress conditions.
Keywords: Calcium; Salts; Carbohydrates; soli; Proteins; vápník; oxid dusnatý; Salt tolerance; Nitric Oxide; nitroprusid; Seed germination; Amylase; solný stres; Seeds; Germination; peroxid vodíku; Salt Stress; Amino acids; chlorid vápenatý; Calcium Chloride; Nitroprusside; klíčení; Chenopodium quinoa; Hydrogen Peroxide; semena rostlinná